Learning in Higher Education and Financial Literacy in Shaping Makassar State University Students’ Financial Behavior - Andi Mustika Amin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Students’ financial behavior has become an important issue in higher education because university students are increasingly exposed to diverse financial responsibilities, digital financial services, consumer lifestyles, and decisions related to savings, spending, and income management. This study aims to explore how learning in higher education and financial literacy shape the financial behavior of Makassar State University students. A qualitative descriptive-exploratory approach was employed to understand students’ experiences, meanings, and everyday practices in managing personal finances rather than statistically testing relationships between variables. The informants were active Makassar State University students who had experience managing personal finances from pocket money, scholarships, additional income, or other economic activities. Data were collected through in-depth interviews, limited observations, and documentation, and were analyzed using thematic analysis. The findings indicate that learning in higher education provides students with basic knowledge of financial concepts, including planning, record-keeping, money management, entrepreneurship, and economic decision-making. However, such learning does not fully shape financial behavior when it remains theoretical and is mainly oriented toward corporate or organizational contexts. Financial literacy helps students distinguish needs from wants, prioritize spending, save, control consumption, and consider financial risks. Students’ financial behavior is also shaped by personal habits, peer environment, lifestyle, self-control, and the use of digital financial services. The study concludes that financial behavior is formed through the interaction of education, literacy, and daily financial practices. Its implication is the need for more contextual, applicable, and student-centered financial learning in higher education.